The Effect of Ramadan Fasting on Body Composition and Metabolic Syndrome in Apparently Healthy Men - Al-barha, Naif S. (Am J Mens Health, 2018)
There are few studies investigating the role of Ramadan fasting on body composition and the characteristics of metabolic syndrome, especially in hot environments. The main aim of the study was to investigate the effect of Ramadan fasting on body composition and the characteristics of metabolic syndrome in apparently healthy men. In a randomized design, 44 college students aged 27.6 ± 5.8 years were selected to participate in the present study. Lifestyle was assessed by a developed questionnaire, body composition was measured using a bioelectrical impedance analyzer, and blood parameters were evaluated by taking a vein blood sample (10 ml) after fasting 10 hr. All measurements were taken 2–3 days before the month of Ramadan, at the end of Week 2 and end of Week 3, and 6 weeks later. The results identified no significant changes in any of the body composition parameters before, during, or after the month of Ramadan. The only significant change in blood parameters was recorded as a positive reduction in low-density lipoprotein (LDL) during the month of Ramadan, compared to before and after Ramadan. No major changes in metabolic syndrome factors were seen except in fasting blood glucose and systolic blood pressure as both factors were slightly but significantly elevated during the month of Ramadan and even after Ramadan, though both of them were within normal levels. This study concludes that Ramadan fasting could be one of the factors that reduce LDL. More studies are needed to clarify the role of Ramadan fasting on different populations such as obese and diabetic patients.